Psychometric properties of the Tinnitus Functional Index (TFI): assessment in a UK research volunteer population - Fackrell, Kathryn L.; Hall, Deborah A.; Barry, Johanna G.; Hoare, Derek J. (Elsevier, 2016)
Objectives